The Effect Of Current Ratio (CR) And Debt To Asset Ratio (DAR) On Return On Equity (ROE) At Pt Telkom Indonesia (TELKOM) Persero Tbk For The Period 2006 – 2024 - Fadli, Achmad Agus Yasin; Rahman, Fitria Annisa (Journal of Management, Economic, and Accounting, 2025)
This research aims to determine the effect of Current Ratio (CR) and Debt to Asset Ratio (DAR) on Return On Equity (ROE) both partially and simultaneously at PT Telkom Indonesia (Telkom) Persero Tbk. The research method used is a quantitative method. The population in this study is all annual financial reports of PT Telkom Indonesia (Telkom) Persero Tbk. The sample used in this study is the financial position report and income statement from 2006 to 2024. The data analysis techniques used are descriptive analysis, classical assumption test, determination coefficient test, multiple linear regression analysis, and hypothesis test. The results of this study indicate that partially the Current Ratio (CR) variable has no effect and is not significant on Return On Equity (ROE) at PT Telkom Indonesia Tbk. While partially the Debt to Asset Ratio (DAR) variable has an effect on Return On Equity (ROE). Current Ratio (CR) and Debt to Asset Ratio (DAR) together do not have a significant effect on Return On Equity (ROE) at PT Telkom Indonesia Tbk. for the period 2006 – 2024.